Inequality and outside options in common-property resource use. - Tarui, Nori (Journal of Development Economics, 2007)
Using a dynamic intergenerational game, this paper analyzes the effects of inequality among resource users and their access to outside markets and credit on cooperative use of a local commons. The study finds that, depending on the agents' harvest sharing rule, the conditions under which homogeneous agents can cooperate in equilibrium may not be sufficient for cooperation when agents differ in harvesting productivity. The resource users' access to outside markets or credit may have a negative effect on efficient local resource management. Copyright (c) 2006 Elsevier B.V.